Motivasi anggota kelompoktani dalam peningkatan fungsi kelompoktani padi sawah di Kecamatan Bendahara Kabupaten Aceh Tamiang - Herawaty Herawaty; Ameilia Zuliyanti Siregar; Nadia Br Simanjuntak (Jurnal Sosial Ekonomi Pertanian, 2022)
The purpose of this study is to know the level of motivation of farmers regarding the function of gruptani and the factors that influence the motivation of farmers in farmer groups. The research was conducted by the Treasurer of Aceh Tamiang Regency, Aceh Province and was conducted in April 2021. Data collection method with interviews, observations and questionnaires that have been tested for validity and reliability, with data analysis methods using Likert scale and Multiple Linear Regression Test. The results showed the motivation level of rice paddy farmers regarding the function of gruptani is very high with a percentage of 84%. The Variables of Age, income, education and land area were variables that had significant effect on motivation of groupfarmer membera on ricefield. Meanwhile, knowledge variables had no partial significant effect in this study.